Approaching the Yearly Expenses of Students Registered on UNED, Costa Rica - Gómez Hernández, Alexandra (2022)
The indicator of expenditure per student is used to measure the efficiency of educational processes in most countries. In Costa Rica, efforts have been made to establish a common methodology that allows comparison between state universities: a task that has not yet been completed. This article aims to provide an approximate figure of the cost per student a Costa Rican public university, the Universidad Estatal a Distancia (UNED), taking as reference the related available documents and using the information provided by the budget control office of the institution. The results indicate that, at UNED, the expenditure per student as a percentage of GDP per capita is 18,35% for 2018 and 87,6% of the total FEES allocated to the institution in that year.